Ice Camp (PRELIMINARY) AERI data. (GIF). Version 1.0 [PRELIMINARY] ... - Atmospheric Radiation Measurement ARM User Facility; Atmospheric Radiation Measurement ARM User Facility (UCAR/NCAR - Earth Observing Laboratory, 2007)
This data set contains PRELIMINARY data from the ARM Atmospheric Emitted Radiance Interferometer (AERI). Data are GIF images of temperature plots from selected days. ...